2012
DOI: 10.1037/a0026279
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exposure therapy for combat-related posttraumatic stress disorder: Comparing outcomes for veterans of different wars.

Abstract: There is significant support for exposure therapy as an effective treatment for posttraumatic stress disorder (PTSD) across a variety of populations, including veterans; however, there is little empirical information regarding how veterans of different war theaters respond to exposure therapy. Accordingly, questions remain regarding therapy effectiveness for treatment of PTSD for veterans of different eras. Such questions have important implications for the dissemination of evidence based treatments, treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 22 publications
7
61
0
Order By: Relevance
“…Older veterans did have significantly higher self-reported PTSD symptoms, but that main effect was not present in the final multilevel model due to the inclusion of initial PTSD symptom severity as a separate variable. Prior studies Yoder et al, 2012) Race/Ethnicity and treatment outcomes. Regarding the association between race/ethnicity and treatment outcomes, there have been some conflicting results in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older veterans did have significantly higher self-reported PTSD symptoms, but that main effect was not present in the final multilevel model due to the inclusion of initial PTSD symptom severity as a separate variable. Prior studies Yoder et al, 2012) Race/Ethnicity and treatment outcomes. Regarding the association between race/ethnicity and treatment outcomes, there have been some conflicting results in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have been conducted with combat veterans in the VA system (Eftekhari et al, 2013;Goodson et al, 2013;Rauch et al, 2009;Tuerk et al, 2011;Yoder et al, 2012). All of the effectiveness studies carried out with vetrans have shown that PE is an effective treatment for PTSD.…”
Section: Psychotherapies For Ptsdmentioning
confidence: 99%
“…First, Tuerk et al (2011) showed large reductions in self-reported PTSD symptoms from pre-to post-treatment in OIF/OEF veterans (N = 65). Second, to examine possible differences in effectiveness across military cohorts, Yoder et al (2012) compared PE outcomes for new veterans, Persian Gulf war veterans, and Vietnam veterans (N = 112). Effect sizes were large for all three groups, and largest in new veterans.…”
Section: Intervention Studies In Veteransmentioning
confidence: 99%
“…[7][8][9][10][11] PE demonstrates effect sizes of over 1 standard deviation improvement from baseline in intent-to-treat samples and 2 standard deviations improvement for treatment completers. 7,8,10,[12][13][14][15] Moreover, the protocol has been shown to be particularly effective in normative treatment settings for Operation Enduring Freedom (OEF)/Operation Iraqi Freedom (OIF)-related PTSD. 10,[12][13][14][15] Failing to diagnose and treat stress disorders in combat settings represents a missed opportunity, as time-limited treatment can increase functionality, 16 decrease the need for future mental health services, 17 and, in cases of ASD, prevent the subsequent onset of PTSD.…”
mentioning
confidence: 99%